The Effectiveness of Peer Education and Instagram Nutrition Education on Changes in Knowledge and Consumption of Risky Foods in Students - Erina Masri; Marisa Aulia Tunnisa; Dezi Ilham (Universitas Ibn Khaldun Bogor, 2023)
Risky foods are foods that include foods high in sugar, salt, and fat that are consumed in excess. The results of Riskesdas showed excessive sugar consumption of as much as 53.1%, excess salt at 26.2%, and excess fat at 26.2%. This study aims to determine the difference in the effectiveness of nutrition education using peer education methods compared to education using Instagram media on knowledge and consumption of risky foods in University X Students in Padang City. Types of research Quasy Experiment, two group pretest-posttest design. The first group was given intervention through peer education A total of 12 samples and the second group were given intervention through media instagram, A total of 12 samples. The sampling techniques used are purposive sampling. Knowledge and consumption of risky foods were measured through interviews using questionnaires and the SQ-FFQ form. Data analyzed by test Paired sample t-test, Wilcoxon, and Mann Whitney. It was found that there was an influence of nutrition education using peer education On knowledge (p = 0.005), there is an influence peer education against food consumption (p = 0.000). As well as there is influence of media instagram On knowledge (p = 0.000), there is an influence media Instagram against food consumption (p = 0.000). There is no difference in the effectiveness of peer education with media Instagram against changes in knowledge (p = 0.311) and consumption of risky foods (p = 0.908). Method peer education and media Instagram are effective for changing knowledge and consumption of risky foods in students.